Flow-down of safety from general contractors to subcontractors working on commercial construction projects. (October 2021) - Dale, Ann Marie; Barrera, Marco; Colvin, Ryan; Strickland, Jaime; Evanoff, Bradley A.
Abstract: Small and medium construction firms have high injury rates but lack resources to establish and maintain effective safety programs. General contractors with exemplary safety programs may serve as intermediaries to support development of smaller firm's safety programs. The purpose of this study was to examine the flow-down influence of general contractors' safety programs on the safety climate and safety behaviors among workers employed by small and medium sized subcontractors. This study collected workers' perception of safety climate and safety behaviors while working on projects with general contractors with exemplary safety programs and other general contractors. We also documented the safety program policies and practices of subcontractors, and recorded the changes in safety policies required from general contractors with exemplary programs. We examined differences in safety program changes between small and medium sized subcontractors. Results showed workers perceived general contractors with exemplary safety programs had stronger safety climates than other general contractors. Smaller subcontractors had less robust safety programs with fewer safety elements than larger subcontractors, and therefore, many of the smaller subcontractors had to adopt more safety policies and practices to work for general contractors than large subcontractors. These findings suggest that general contractors with robust safety programs can serve as intermediaries and influence the development of the safety programs of small sized firms. Future work will need to determine if smaller firms eventually adopt safety policies and practices as part of their permanent safety program.